Group Behavior and Development: A Comparison of Farmers' Organisations in South Korea and Taiwan - Larry Burmeister; Gustav Ranis; Michael Wang (Yale University, Economic Growth Center, 2001)
This study presents a comparative analysis of farmers' organisations in Korea and Taiwan during 1950-80 in order to help us understand the role of group behavior in affecting development outcomes. It highlights the linkages between group behavior, parastatal organisational structures and economic performance. The paper examines the historical and political economy contexts that led to the creation of both countries' farmers' organisations and highlights the institutional characteristics that impacted their operational effectiveness. The study discusses elements in internal and external policies that affected group motivation and traces the implications of such differences in group behavior for bottom line performance. Though there existed many similarities in both organisational structure and operations, it is argued that differential intra-group behavioral dynamics led to differences in agricultural performance. Although, with the declining importance of agriculture, the relative importance of such organisations has declined in recent years, the study is relevant for developing countries at every stage of development.
Keywords: O17; 330; Farmers' Organizations; Korea; Taiwan; Group Behavior; Landwirte; Interessenvertretung; Landwirtschaftliche Entwicklung; Südkorea; Taiwan